Exploring Sundanese Cultural Heritage: An Analysis of Wayang Golek Stories in the Islamization of West Java - Iryana, Wahyu; Sujati, Budi; Ningsih, Arum (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2025)
Wayang Golek is one of the Sundanese cultural forms derived from the Indian epics, the Mahabharata and Ramayana. The Sundanese Wayang Golek originated from the long process of Sunan Kalijaga's preaching journey, which spread Islam through culture. The Wayang Golek performance is told by puppeteers who provide entertainment, spectacle, and guidance for the community. The play that is very memorable and in demand by wayang fans is the Jamus Layang Kalimahsahda play, which is phenomenal. People who have the Jamus Layang Kalimahsahda will become invincible. This article presents a Critical review of the Teachings of Tauhidan Habluminallah, exploring the process of horizontal communication between humans and God, combined with cultural narratives. The methods used are literature review, observation, and interviews. The initial conclusion describes how the Sundanese wayang golek serves as a cultural ritual that guides society with the teachings of tauhid and the philosophy of life in the world. ملخص وايانغ جوليك هو شكل من أشكال الثقافة السوندية، متجذر في الملاحم الهندية، المهابهاراتا ورامايانا. نشأ وايانغ جوليك السوندية من مسيرة الدعوة الإسلامية الطويلة لسونان كاليجاغا، التي نشرت الإسلام عبر الثقافة. يؤدي عروض وايانغ جوليك محركو الدمى (الدالانغ)، الذين يقدمون الترفيه والعروض المسرحية والإرشاد للمجتمع. ومن المسرحيات التي لا تُنسى والمرغوبة بشكل خاص بين محبي وايانغ مسرحية